Pemetaan Sistem Hukum Kesultanan Kutai Kertanegara - Makmun Syar'i (Faculty of Sharia UIN Kiai Ageng Muhammad Besari Ponorogo, 2007)
This study aims to map the legal system of the Kutai Kertanegara Sultanate and understand the legal characteristics that developed in the kingdom. This study explores the sources of law, the structure of the judiciary, and the interaction between customary, Islamic, and colonial law in the legal system of the Kutai Kertanegara Sultanate. The research methods used were library research and historical analysis with a descriptive-analytical approach. The main sources of this research include legal manuscripts, historical records, and previous research related to the law of the Kutai Sultanate. The results showed that the legal system of the Kutai Kertanegara Sultanate was a combination of Dayak-Malay customary law, Islamic sharia, and the influence of Dutch colonial law. This synergy created a dynamic legal system that was adaptive to the changing times. This study contributes to the understanding of the history of Indonesian law and its relevance in the context of customary law and contemporary Islamic law.